Pengaruh Green Brand Ambidexterity terhadap Customer Satisfaction - Santoso, Mikona Brillia; Arafah, Willy (BUDGETING : Journal of Business, Management and Accounting, 2024)
Environmentally friendly brands have rapidly become a growing phenomenon in recent years. Consumers are increasingly aware of the environmental impact of their purchases and are seeking eco-friendly products and services. This has led many companies to develop and market green brands. This study investigates how green brand ambidexterity, defined as a company's ability to balance the exploitation of existing green capabilities with the exploration of new green opportunities, affects customer satisfaction through perceived brand performance and green trust. Data was collected from 116 respondents and analyzed using SmartPLS. The results indicate that green brand ambidexterity positively influences perceived brand performance and green trust, which in turn enhances customer satisfaction. These findings make a significant contribution to the green marketing literature by demonstrating that green brand ambidexterity is a crucial mechanism for achieving customer satisfaction in the context of green brands. Keywords: Green Brand Ambidexterity, Perceived Brand Performance, Green Trust, Customer Satisfaction.